An overview of the changes and practices in the Japanese human resource management - Abdullah, Rashid; Ahmad, Zalena; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
Japanese organizations combine the concepts of "competition" and "co-operation". They believe in long-term relationships and trust their workers and vendors. It is argued that because of the practice of single or dual sourcing, there is a tendency for high inter-dependence between assembler or automaker and suppliers. On the other hand, because of specialized capital investment, suppliers are highly dependent on the assembler (market dependency). In analyzing the diffusion or transferability of Japanese technology, some authors taken it as the supreme model and used it as a benchmark while other regards the Japanese software technology transfer as a discrimination model between Japanese. Early research on industrial organization tended to emphasize the cultural uniqueness of Japanese firms i.e. industrial relations, lifetime employment, and seniority wages and enterprise unionism were all proclaimed as uniquely Japanese and explained by cultural features. Recently, economists have explained Japanese industrial characteristics based on new developments in industrial organization research.